Midden site selection in Dorcas gazelle: Larger is not always better. Issue 20 (22nd September 2021) - Soultan, Alaaeldin; Nagy, Abdullah; Attum, Omar
Abstract: Dorcas gazelles are believed to use middens to mark their territories and transmit information. Given the commitment to maintaining a midden, it is believed that middens are not placed randomly. We examined how the habitat (tree height and maximum canopy) and anthropogenic disturbance (camel and human presence) influenced the selection of midden sites by Dorcas gazelles in South Sinai, Egypt. Our results showed that Dorcas gazelles did not place middens at larger trees, while favoring relatively smaller trees and shrubs where the anthropogenic disturbance and perceived hunting risk are less. Our results, in light of the previous findings, suggest that selection of midden sites is species context‐dependent behavior. In areas with less anthropogenic disturbance and hunting, Dorcas gazelles have been shown to select the largest trees of the same species as midden sites. In contract, in our study site with high anthropogenic disturbance and no protection from hunting, gazelles did not utilize the presumably optimum landmarks for midden sites. Our study showed that Dorcas gazelles instead utilized smaller trees and some shrubs that are less conspicuous and presumably less effective as advertisement sites, but safer. Abstract : In this research, we examined how habitat and anthropogenic disturbance influenced the selection of midden sites by Dorcas gazelles. We found evidence that Dorcas gazelles avoid utilizing the presumably optimum landmarks for midden sites and instead utilized smaller trees and some shrubs that are less conspicuous and presumably less effective as advertisement sites, but safer.